Synthesis of azaheterocycles by Cu-catalyzed aerobic alkene diamination and tempo-mediated aliphatic C-H oxidation - Zhu, Xu (2015)
Due to the significance of nitrogen-containing heterocycles (azaheterocycles) in biology, medicine and materials science, it is important to invent robust methodologies for synthesis of azaheterocycles using readily available nitrogen-containing starting materials in unprecedented fashions. This thesis describes methodology development for synthesis of azaheterocycles using intramolecular tactics by 1) copper-catalyzed aerobic synthesis of bi- and tricyclic amidines via intramolecular diamination of acyclic N1-pentenylamidines, and 2) TEMPO-mediated remote aliphatic C–H oxidation (oxygenation and amination) with oximes and hydrazones as the corresponding O- and N-radical precursors, respectively. This operationally simple process enables the concise assembly of substituted isoxazole, pyrazole, and hydropyridazine skeletons